Pelatihan Bahasa Inggris Dalam Pemasaran Online Guna Membangun Jiwa Wirausaha Perempuan - Kuspiyah, Hastuti Retno; Amaliah, Khusnatul; Kurniati, Nia; Marsa, Shela Septina; Ariansyah, Rio Tegar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STKIP Nurul Huda, 2021)
English training in online marketing to build the entrepreneurial spirit of women during the Covid-19 Pandemic, PRIMA Village was carried out as a form of solution related to problems due to the impact of the world economy. The training activities took place at the village hall with the target of PRIMA women at Tumijaya village. Based on the results,, it was found that this activity received a positive response from the village and the participants. It is an effort to facilitate learning to better manage businesses, gain economic benefits from their activities and learn from one another. With the English language training activities for PRIMA women in Tumijaya village, it is a form of concern to help them find their potential and provide knowledge for readiness to build an entrepreneurial spirit as well as an effort to realize the ideals of entrepreneurship in order to realize gender equality and justice during the Covid-19 pandemic.